1971
DOI: 10.2337/diab.20.7.490
|View full text |Cite
|
Sign up to set email alerts
|

Severe Diabetic Ketoacidosis (Diabetic “Coma”): 482 Episodes in 257 Patients; Experience of Three Years

Abstract: There were 340 episodes of severe diabetic ketoacidosis in 257 patients, July 1, 1965 to June 30, 1968. Fatality in thirty-two cases was associated with significantly elevated admission serum glucose, urea nitrogen, osmolality and age. Major associated causes of death were infection and myocardial infarction. Twenty episodes of acute pancreatitis, with only two deaths, demonstrated severe morbidity and marked elevation of serumglucose and urea nitrogen. Fourteen of the twenty occurred in alcoholics. There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
3

Year Published

1973
1973
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(44 citation statements)
references
References 0 publications
1
39
1
3
Order By: Relevance
“…3 the acutely ketotic alloxan diabetic rat is severely ill with marked hypoglycemia and hyperketonemia. The initial plasma glucose concentrations in the three groups of animals at zero time clustered around 1,000 mg/100 ml, a figure much higher than that found in pancreatectomized diabetic rats (19) but very close to values seen in severe human disease (20). Mean plasma ketone levels were greater than 1,500 /mol/100 ml.…”
Section: Resultsmentioning
confidence: 51%
“…3 the acutely ketotic alloxan diabetic rat is severely ill with marked hypoglycemia and hyperketonemia. The initial plasma glucose concentrations in the three groups of animals at zero time clustered around 1,000 mg/100 ml, a figure much higher than that found in pancreatectomized diabetic rats (19) but very close to values seen in severe human disease (20). Mean plasma ketone levels were greater than 1,500 /mol/100 ml.…”
Section: Resultsmentioning
confidence: 51%
“…Although it has previously been noted that haemostatic problems are frequently seen in patients with DKA [40,41], studies related to the haemostatic system in these patients are rare and not sufficient in content. Beigelman [40] found that 25% of all mortalities during severe DKA were caused by coronary artery thrombosis, which was the most common cause of death together with infections.…”
Section: Discussionmentioning
confidence: 97%
“…Excessive urinary potassium losses, which occur as a result of osmotic diuresis with increased delivery of fluid and sodium to potassium secretory sites in the distal nephron, are ultimately responsible for the development of potassium depletion (177)(178)(179)(180). Secondary hyperaldosteronism and urinary ketoanion excretion, as potassium salts, further augment potassium losses.…”
Section: Potassiummentioning
confidence: 99%
“…Table 2 shows typical potassium deficits, which represent mainly intracellular losses, in both DKA and HHS. Extracellular hyperosmolarity, secondary to hyperglycemia, causes a shift of water and potassium from the intracellular to the extracellular space, resulting in normal or elevated serum potassium concentrations despite total-body potassium deficits of 500-700 mEq/l (44,(177)(178)(179). This potassium shift is further enhanced by insulin deficiency and the presence of acidosis and accelerated breakdown of intracellular protein (180).…”
mentioning
confidence: 99%